Trends in the Implementation of Algorithmic Thinking in Social Sciences Research in the Scopus Database: Bibliometric Analysis (1982-2024) - Zafrullah, Zafrullah; Ghany Desti Laksita; Weni Dwi Susanti; Fini Rezy Enabela Novilanti; Resty Aulia; James Leonard Mwakapemba (HISTORICAL: Journal of History and Social Sciences, 2024)
This study aims to look at research trends with the topic of Algorithmic Thinking conducted using bibliometric analysis. By using predetermined keywords, 158 documents in the Scopus database were analyzed using R Program and VOSviewer. From the results of the analysis that has been carried out, it can be concluded that this study covers the period 1982 to 2024, which covers a span of 42 years. Korea University and National Taiwan Normal University based in Seoul and Taipei topped the list with the same number of publications at 8 publications. Chung-Yuan Hsu from Taiwan's National Pingtung University of Science and Technology tops the list with an h-index of 2, supported by a total of 63 citations and 3 publications. The journal “Educational and Information Technology”, ranked second with an h-index of 6, supported by a total of 274 citations and 13 publications. Grover et al. (2015) is the source with the highest citations, with 235 citations. There are 28 keywords grouped into four clusters, with the keywords Arduino, Computational Thinking Skills, Early Childhood, Mathematics, and Curriculum used as recommendations for further research related to Algorithmic Thinking.